Recent Patents in Bionanotechnologies: Nanolithography, Bionanocomposites, Cell-Based Computing and Entropy Production - Layton, B.
This article reviews recent disclosures of bio-inspired, bio-mimicked and bionanotechnologies. Among the patents discussed is a nanoscale porous structure for use in nanocomposites and nanoscale processing. Patents disclosing methods for printing biological materials using nanolithography techniques such as dip-pen technology are discussed, as are patents for optimizing drug design. The relevance of these technologies to disease prevention, disease treatment and disease resistance is discussed. The paper closes with a review of cell-based computing and a brief examination of how information technology has enabled the development of these technologies. Finally, a forecast of the how these technologies are likely to accelerate global entropization is discussed as well as a new classification of machine types.
Keywords: BIONANOTECHNOLOGY; BIOMIMICKERY; BIO-INSPIRED; DIP-PEN; NANOTECHNOLOGY; PRINTING; INFORMATION; ENTROPY